Enabling Environment Assessment and Baseline for Scaling Up Handwashing Programs : Tanzania - Hooks, Carol (World Bank, Washington, DC, 2014)
To follow up country work supported by the Public-Private Partnership for Hand-washing (PPPHW), the World Bank Water and Sanitation Program (WSP) received funding from the Bill and Melinda Gates Foundation to support projects to scale up the promotion of hand-washing with soap (HWWS) in Peru, Senegal, Tanzania, and Vietnam. The major project objectives of the hand-washing initiative are: i) inculcate the HWWS habit among millions of mothers and children in these countries; ii) use a strong monitoring and evaluation (M&E) component to enhance the conceptualizing and management of such programs; and iii) establish sustainable programs that will continue and expand after this four-year grant ends. Enabling environment assessments were carried out in all four countries to assess current conditions for scalability and sustainability and to make recommendations for improving conditions that are not supportive. This report summarizes the study in Tanzania. All of the country studies followed a similar methodology, developed by the WSP, to examine nine dimensions of scalability/sustainability through individual and group in-depth interviews and a survey in which respondents are asked to score various statements. The project also engages other relevant ministries. Planning, site selection, implementation, and capacity building are being done in consultation with the appropriate government agencies, and the private sector and civil society are being engaged as partners. This four-year project (1.5 years of planning, 2 years of implementation, and 6 months of evaluation) launched with a group of core partners in December 2006, and is expected to take place in 10 districts. The assessment methodology, findings, and recommendations that result from this assessment are documented in this report.